(untitled) (Orfeu, 2017)
This paper presents a review on the article The Social Life of Musical Instruments by Eliot Bates (2012). Bates makes a reflection about organology, criticizes the old classificatory systems, comments on important works about organology and proposes a new paradigm based on the Actor-Network Theory